‘Tainted Pearls of Wisdom’ . A thematic analysis of the representation of women in Egyptian proverbs - El-Nashar, Mohamed; Nayef, Heba; Tayie, Sally Samy; Youssef, Rania Samir (Anàlisi, 2024)
This article discusses the representation of women in Colloquial Egyptian proverbs (CEPs). Even though myriad studies have tackled the image of women in many linguistic genres, this is the first study to discursively examine such portrayal in Egyptian proverbs. Proverbs are usually laden with a moral legacy so instructive that it can steer the rudder of social ideologies. In patriarchal societies, however, sexist proverbs represent women negatively and sediment their submissiveness. The aim of this paper is to explore the major themes in the representation of women in CEPs. To this end, we conducted a thematic analysis of the data from a feminist critical discourse analysis perspective, employing Glick and Fiske’s (2001) Ambivalent Sexism Inventory with its two types of sexism, hostile sexism and benevolent sexism. The data revealed six major themes and 17 subthemes, all exhibiting either hostile or benevolent sexist depictions of women. The data showed that the CEPs were mostly designed to enforce male supremacy over women. Women were portrayed as a source of shame if they did not obey the rules of patriarchal society. While women were objectified and commodified, superficially valuing women for their stereotyped female attributes of domesticity and nurturing of their children, women’s worth is depicted as conditional upon men’s evaluation.